Silsilah hadits dha'if dan maudhu' - Muhammad Nashiruddin Al_Albani (Gema Insani, 1995)
Oen, Jil. I=c.1-3;Jil.II=c.1-5;Jil.3=C.1-3;Jil.IV=c.1-2/ oen, jil.4,c.3; sn,jl.2,c.6, jl.3,c.4-5, jl.4.c,4; ir,jil.1,c.4 ; jil.4,c.5/tr, jil.3=c.6-7/why, .23-.30 (jl. 1= c.5-6, jl. 2= c.7-8, jl. 3= c.8-9, jl. 4= c.6-7)